Public Participation Through Digital Media as a Formof Patriotism During the Pandemic in Indonesia - Sari, Dewi Kartika (UI Scholars Hub, 2021)
The global development of social media creates public participation, including during the pandemic. In Indonesia, public participation by digital media occurred and developed through the ‘Warga Bantu Warga’ [Support Each Other] project, the ‘Urun Daya Covid’ [Covid Crowdsource] initiative, and the ‘Bagi Rata’ [Cross Subsidization] initiative. People engage in a sense of solidarity among relatives, friends, neighbors, even with strangers they do not know. This study aimed to explain forms of public participation using digital media where patriotism could be observed in citizens’ activities. Public participation and aspects of patriotism are the concepts used in this study. The research applied a netnographic approach and it is an explanatory research. The study results show that people use digital media as a means of participation and that participation is a form of patriotism. Another finding shows that participation as an expression of patriotism poses challenges in the form of exhaustion in making donations or donation fatigue. Perkembangan global media sosial menciptakan partisipasi publik, termasuk di masa pandemi. Di Indonesia, partisipasi publik dengan media digital terjadi dan dikembangkan melalui proyek ‘Warga Bantu Warga’ [Support Each Other], inisiatif ‘Urun Daya Covid’, dan inisiatif ‘Bagi Rata’ [Cross Subsidization]. Orang-orang terlibat dalam rasa solidaritas di antara kerabat, teman, tetangga, bahkan dengan orang asing yang tidak mereka kenal. Penelitian ini bertujuan untuk menjelaskan bentuk-bentuk partisipasi publik menggunakan media digital di mana patriotisme dapat diamati dalam aktivitas warga. Partisipasi publik dan aspek patriotisme adalah konsep yang digunakan dalam penelitian ini. Penelitian ini menerapkan pendekatan netnografi dan merupakan penelitian penjelasan. Hasil studi menunjukkan bahwa orang menggunakan media digital sebagai sarana partisipasi dan bahwa partisipasi adalah bentuk patriotisme. Temuan lain menunjukkan bahwa partisipasi sebagai ekspresi patriotisme menimbulkan tantangan berupa kelelahan dalam memberikan donasi atau donasi.